2003
DOI: 10.1021/ac034896c
|View full text |Cite
|
Sign up to set email alerts
|

Automated Enzymatic Assays in a Renewable Fashion Using the Multisyringe Flow Injection Scheme with Soluble Enzymes

Abstract: In this paper, a novel flowing stream scheme based upon the multisyringe flow injection (MSFI) technique is presented as a powerful tool to perform automated enzymatic assays. The exploitation of enzymes in homogeneous phase circumvents typical drawbacks associated with the commonly used packed-bead or open tubular permanent columns, namely, malfunctions of the reactor, carryover effects, flow resistance, loss of binding sites, large reagent consumption, and use of harmful organic solvents during immobilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Moreover, about half of the applications described rely on UV-visible spectrophotometric detection. 4,5,8,12,14,15,18,[20][21][22][23][24][25] Other types of detection systems were also applied in-line, namely those based on chemiluminescence, [26][27][28][29] potentiometry, 30 fluorometry, 17,31 hydride generation atomic fluorescence spectrometry [32][33][34][35] (HGAFS) and optical fiber reflectance. [36][37][38] In the following sections, some features of MSFIA systems incorporating an inline sample treatment are discussed and compared to those obtained in FIA and SIA systems.…”
Section: Applications Using Msfia Systemmentioning
confidence: 99%
“…Moreover, about half of the applications described rely on UV-visible spectrophotometric detection. 4,5,8,12,14,15,18,[20][21][22][23][24][25] Other types of detection systems were also applied in-line, namely those based on chemiluminescence, [26][27][28][29] potentiometry, 30 fluorometry, 17,31 hydride generation atomic fluorescence spectrometry [32][33][34][35] (HGAFS) and optical fiber reflectance. [36][37][38] In the following sections, some features of MSFIA systems incorporating an inline sample treatment are discussed and compared to those obtained in FIA and SIA systems.…”
Section: Applications Using Msfia Systemmentioning
confidence: 99%
“…35,36 GOD and glucose are still of great importance as analyte recognition systems in biosensors. 35,36 Each system was optimized to various working parameters.…”
Section: Determination Of Glucose In Human Serummentioning
confidence: 99%
“…35,36 GOD and glucose are still of great importance as analyte recognition systems in biosensors. 35,36 Each system was optimized to various working parameters. The impact of various buffers on the catalytic reaction system was examined, and the results showed that the activity of these composite nanoparticles in NH3-NH4Cl medium was higher than that in other buffers.…”
Section: Determination Of Glucose In Human Serummentioning
confidence: 99%
“…Because the TDMBA system is the most sensitive and stable, it was chosen for the determination of glucose. Comparing with the methods reported (Table 3), [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] this RS bioassay for glucose had higher sensitivity, and the substrate was easily obtained. …”
mentioning
confidence: 99%
“…1 Exact, rapid and quantitative determinations of glucose are thus essential in the diagnosis and management of diabetes. At present, several assays have been reported for the determination of glucose, including chemiluminescence (CL), [2][3][4][5][6][7] spectrophotometry, [8][9][10] electrochemical methods, 11,12 fluorescence methods 13,14 and others. [15][16][17] A sensitive CL method was reported for the determination of 2 × 10 -8 -1 × 10 -4 mol/L glucose, and some metal ions catalyzed the luminol CL reaction.…”
mentioning
confidence: 99%